Methods of reducing the obstacles facing families of Quadriplegia patients from the viewpoint of families and social workers - Alsaloom, Waleed Abdullah (Journal of Humanities & Social Sciences, 2020)
The study aimed to know the methods of reducing the obstacles facing the families of quadriplegic patients in the Kingdom of Saudi Arabia from their point of view and from the point of view of social workers. To achieve the goal of the study, the researcher used the Social Survey Methodology, and the study sample consisted of (120) of the families of quadriplegic patients, in addition to (70) social workers, and the researcher used the questionnaire as a study tool. The results of the study showed that the families of those with quadriplegia agree to methods of reducing obstacles that confront them with an average of (4.08) and that the most important of these methods are as follows: Increasing the social worker’s awareness of the professional intervention methods during the crisis, the need for the social worker to understand the tasks that he must perform towards the families of quadriplegic patients, educating the families of the importance of the social worker’s intervention and revealing the problems they face, especially social and economic, providing training courses for the specialist on support methods for families of quadriplegia patients. The results of the study also showed the approval of the social workers on methods to reduce the obstacles facing families of quadriplegia patients with an average of (4.04), and the most important of these methods are the following: Increased awareness of the social worker with methods of professional intervention during the crisis, the need for the social worker to understand the tasks that he must perform towards the families of quadriplegic patients, Sensitizing families on the importance of social worker intervention and revealing problems they face, especially social and economic, providing training courses for the specialist on methods of support for families of quadriplegia patients.